Hubungan lama kerja dengan perilaku bidan dalam melakukan pencegahan perdarahan postpartum di Kabupaten Bantul - Diah Nur Anisa; Detty S Nurdiati; Wiwin Lismidiati (STIKes Surya Global Yogyakarta, 2019)
Postpartum hemorrhage is one of the causes of the hight of the maternal mortality rate (MMR) in Indonesia. Maternal mortality in Bantul regency has been increased than the last. The incident of prevention of midwives in the prevention of postpartum hemorrhage during labor proses. To find out the relationship between the length of work and the behavior of midwives in the prevention of postpartum hemorrhage in Bantul regency. This study included a type of correlation study with a cross sectional design. The sampling technique in this study used probability sampling with cluster sampling totaling 68 midwives in five health centers. Retrieval of data in this study used an observation sheet to see the actions of midwifes in conducting active management in the third stage as preventive measure for postpartum hemorrhage and the identity sheet of respondents to see the length of work that had been undertaken by midwives. The result of this research showed that the mayority of midwives who have length work ≥ 10 years, it was 47 people (69%), and midwives who have good behavior in prevention of postpartum hemorrhage was 40 people (58,8%). The result of correlation test between length work and midwives behavior in prevention of postpartum hemorrhage obtained p = value 0,851 (p 0,05). There no relatinship of long work with the behavior of midwives in theprevention of postpartum hemorrhage in Bantul regency.